Copper-clad laminate and method for producing the same
The copper-clad laminate, featuring a low-dielectric resin film and an electroless copper plating layer with surface modifications via vacuum plasma treatment, addresses the challenge of achieving high adhesion and low transmission losses in flexible circuit boards.
Patent Information
- Application Number
- JP2023147907
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-12
- Publication Date
- 2025-03-25
AI Technical Summary
Existing methods for manufacturing flexible circuit boards using low-dielectric resin films face challenges in achieving high adhesion between the resin film and the electroless copper plating layer while minimizing transmission losses.
A copper-clad laminate is developed, featuring a low-dielectric resin film with a relative permittivity of less than 3.2 or 3.2 or more at 10 GHz, and a dielectric loss tangent of 0.008 or less, combined with an electroless copper plating layer. The surface modification of the resin film is achieved through vacuum plasma treatment, followed by the application of a Pd support layer and electroless copper plating.
The proposed solution ensures high adhesion between the low-dielectric film and the electroless copper plating layer, effectively suppressing transmission losses, and achieving an adhesion strength of 3.5N/cm or more in tape peeling tests.
Smart Images

Figure 2025040846000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a copper clad laminate for use in a flexible circuit board mounted on a communication device or the like, a method for producing the same, and a flexible circuit board made from the copper clad laminate. [Background technology]
[0002] In recent years, electronic devices have become increasingly smaller and more powerful, and this is due in large part to the development of communication devices that use radio waves, such as mobile phones and wireless LANs. In particular, with the increasing volume of information, as exemplified by big data generated by the IoT, communication signals between electronic devices are becoming increasingly high-frequency, and the circuit boards mounted on such communication devices require materials with low transmission loss (dielectric loss) in the high-frequency range.
[0003] It is known that the dielectric loss that occurs in this circuit board is proportional to the product of three elements: "signal frequency," "square root of the dielectric constant of the board material," and "dielectric loss tangent." Therefore, to obtain the above-mentioned excellent dielectric properties, a material with as low a dielectric constant and dielectric loss tangent as possible is necessarily required.
[0004] In such circuit boards, the circuits are generally formed of a metal such as copper. The copper layer in the circuit board is formed by, for example, a lamination method as disclosed in Patent Document 1, a casting method as disclosed in Patent Document 2, or a plating method as disclosed in Patent Document 3. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent No. 6202905 [Patent Document 2] Patent No. 5186266 [Patent Document 3] JP 2002-256443 A [Patent Document 4] International Publication No. 2021 / 039370 [Patent Document 5] International Publication No. 2022 / 030644 [Patent Document 6] International Publication No. 2022 / 030645 Summary of the Invention [Problem to be solved by the invention]
[0006] As mentioned above, reducing transmission loss in high-frequency communications has become an important development element in recent years, and resin films with low transmission loss (hereinafter also referred to as "low dielectric films" or "low dielectric resin films") are beginning to be used as base materials for flexible circuit boards. Such flexible circuit boards (hereinafter also referred to as "FPCs") are manufactured by forming a conductive coating of copper or the like on a low dielectric film, for example, by sputtering, plating, etc. When manufacturing FPCs by sputtering, the manufacturing process becomes complicated, leaving many issues unresolved in terms of productivity and cost.
[0007] In contrast, according to the plating methods shown in Patent Documents 3 to 6, a relatively good adhesion between the copper layer and a resin film having a high dielectric constant can be ensured. On the other hand, in these patent documents, a surface modification step is carried out in which a mixed solution of an alkaline aqueous solution and an amino alcohol is applied to the surface of the resin film. As a result of continued investigations by the present inventors, it was concluded that such surface modification by wet treatment alone does not necessarily lead to good cleavage of molecules present on the surface of the resin film or generation of functional groups, and there are cases in which a catalyst, which is a deposition nucleus for electroless Cu plating, cannot be supported on the film surface.
[0008] The present invention aims to solve the above-mentioned problems as an example, and aims to provide a copper-clad laminate and a manufacturing method thereof that can achieve high adhesion between a low dielectric resin film and an electroless copper plating layer while suppressing transmission loss. [Means for solving the problem]
[0009] In order to solve the above-mentioned problems, a copper clad laminate in one embodiment of the present invention may include a low dielectric resin film having a relative dielectric constant of less than 3.2 at a frequency of 10 GHz and a dielectric tangent of 0.008 or less, and an electroless copper plating layer laminated directly onto at least one surface of the low dielectric resin film.
[0010] In order to solve the above-mentioned problems, a copper clad laminate in one embodiment of the present invention includes a low dielectric resin film having a relative dielectric constant of 3.2 or more and a dielectric loss tangent of 0.008 or less at a frequency of 10 GHz, and an electroless copper plating layer on at least one surface of the low dielectric resin film, and the low dielectric resin film has a peak area (P area2 ) and the peak area (P area1 ) area ratio (P area2 / P area1 ) may be 1.25 or more and 2.00 or less.
[0011] In order to further solve the above-mentioned problems, (10) a method for producing a copper clad laminate in one embodiment of the present invention is a method for producing a copper clad laminate produced by forming an electroless copper plating layer on a low dielectric resin film having a relative dielectric constant of 3.5 or less at a frequency of 10 GHz and a dielectric tangent of 0.008 or less, and may include a step of performing a first surface modification treatment on the surface of the low dielectric resin film by vacuum plasma treatment, and an electroless copper plating step of directly laminating an electroless copper plating layer on the side of the low dielectric resin film that has been surface modified by the vacuum plasma treatment. Effect of the Invention
[0012] According to the present invention, it is possible to ensure high adhesion at the interface between the low dielectric film and the electroless copper plating layer while suppressing transmission loss. [Brief description of the drawings]
[0013] [Figure 1] FIG. 1 is a schematic diagram showing a copper clad laminate 10 (a low dielectric resin film 1 having an electroless copper plating layer 5 formed thereon) in this embodiment. [Diagram 2] FIG. 1 is a schematic diagram showing a copper clad laminate 20 (a low dielectric resin film 1 having an electrolytic copper plated layer 6 and an electroless copper plated layer 5 formed thereon) in this embodiment. [Diagram 3] 1 is a schematic diagram showing the interface state between a low dielectric resin film 1 and an electroless copper plating layer 5 in a copper clad laminate 10 of the present embodiment. [Figure 4] FIG. 1 is a schematic diagram showing the configuration of a vacuum plasma processing apparatus 100 of the present embodiment. [Diagram 5] FIG. 2 is a schematic diagram showing changes in XPS spectrum due to vacuum plasma treatment of SPS. [Figure 6] FIG. 2 is a schematic diagram showing changes in XPS spectrum due to vacuum plasma treatment of PFA. [Figure 7] FIG. 2 is a schematic diagram showing a low dielectric resin film 1 to which catalyst cores 4 have been added after the plasma treatment of the present embodiment. [Figure 8] 1 is a flowchart showing a method for manufacturing the copper clad laminate 10, the copper clad laminate 20, and the flexible circuit board of the present embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] The copper clad laminate of this embodiment will be described below with reference to FIGS. <Copper clad laminate> 1, a copper clad laminate 10 according to this embodiment at least has a low dielectric resin film 1 serving as a base material, and an electroless copper plating layer 5 laminated on at least one surface of the low dielectric resin film 1. As shown in FIG. 2, a copper clad laminate 20 according to this embodiment may have an electrolytic copper plating layer 6 formed on the electroless copper plating layer 5.
[0015] In this embodiment, it is preferable to use a low dielectric resin film having excellent electrical properties in the high frequency range as the low dielectric resin film 1 serving as the substrate. Specifically, the electrical properties of the low dielectric resin film 1 serving as the substrate are preferably a relative dielectric constant of 3.5 or less at a frequency of 10 GHz and a dielectric loss tangent of 0.008 or less.
[0016] More specifically, known resin materials with low dielectric loss can be used as the low dielectric resin film 1. More specifically, among the low dielectric resin films 1 suitable for this embodiment, examples of non-fluorine-based low dielectric resin films that do not contain fluorine and have a relative dielectric constant of less than 3.2 at a frequency of 10 GHz and a dielectric loss tangent of 0.008 or less include cycloolefin copolymer (COC), cycloolefin polymer (COP), syndiotactic polystyrene (SPS), polyphenylene sulfide (PPS), and polyether ether ketone (PEEK). Examples of fluorine-containing fluorine-based low dielectric resin films include polytetrafluoroethylene (PTFE), perfluoroalkoxyalkane (PFA), and the like. Furthermore, among the low dielectric resin films 1 suitable in this embodiment, examples of non-fluorine-based low dielectric resin films that do not contain fluorine and have a relative dielectric constant of 3.2 or more and a dielectric tangent of 0.008 or less at a frequency of 10 GHz include liquid crystal polymers (LCPs).
[0017] As the low dielectric resin film 1, in addition to the above, films of polyimide resin, modified polyimide resin, epoxy resin, polytetrafluoroethylene resin, polyphenylene ether resin, etc. may be used. The resins listed above may be monopolymers or copolymers, and may be used alone or as a composite of a blend of multiple resins. The thickness of the low dielectric resin film 1 is not particularly limited, but is preferably 5 μm to 100 μm in practical use.
[0018] The average surface roughness Ra of the low dielectric resin film 1 at the interface with the electroless copper plating layer 5 is preferably 1.0 nm to 100.0 nm. The average surface roughness Ra of the low dielectric resin film 1 at the interface with the electroless copper plating layer 5 is more preferably 1.0 nm to 70.0 nm, further preferably 1.0 nm to 50 nm, and particularly preferably 1.0 nm to 30 nm. By controlling the average surface roughness Ra within the above range, the transmission loss can be more suitably suppressed.
[0019] Next, the electroless copper plating layer 5 that is directly laminated on at least one surface of the low dielectric resin film 1 will be described. Here, "direct lamination" refers to a lamination mode in which at least a part of the copper layer is in contact with the low dielectric resin film at the interface without the intervention of a known adhesive such as an epoxy resin or a urethane resin. That is, as shown in Fig. 1 and other figures, the electroless copper plating layer 5 of this embodiment is in contact with the low dielectric resin film 1 at the interface, although metal palladium Pd constituting the catalyst cores 4 described below is scattered at the interface. In other words, the electroless copper plating layer 5 of this embodiment is formed on the low dielectric resin film 1 without the intervention of an intermediate layer (the above-mentioned adhesive layer) other than the catalyst core layer.
[0020] [Interface state between low dielectric resin film and electroless copper plating layer] Next, the interface state between the low dielectric resin film 1 and the electroless copper plating layer 5 in this embodiment will be described with reference to Fig. 3. This embodiment is mainly characterized in that, in order to increase the adhesive strength between the copper plating layer and the film, which are directly laminated, a plasma treatment is performed on the low dielectric resin film 1 before lamination to form functional groups 2, and in order to strengthen the adhesiveness of the catalyst cores 4 after the plasma treatment, a Pd-supported layer 3 is formed.
[0021] That is, as exemplified in the above-mentioned patent documents, in the past, when forming an electroless copper plating layer on a low dielectric resin film, surface modification was performed using alkaline hydrolysis (wet process). In this way, it was found that in surface modification of a low dielectric resin film by a wet process, the cleavage of molecules present on the resin surface and the generation of functional groups are not necessarily good, and there is a risk that the palladium catalyst cannot be supported on the film surface afterwards. This means that the Pd complex (catalytic nucleus 4), which serves as the precipitation nucleus of the electroless copper plating layer 5, cannot be supported on the film surface, and if left as is, the electroless copper plating layer 5 with high adhesion cannot be stably formed on the low dielectric resin film 1. Based on such findings, the present disclosure has concluded that the surface of a low dielectric resin film is modified by a dry process using a vacuum plasma treatment as described below.
[0022] As described above, in order to realize good adhesion between the film and the copper plating layer, the process of cutting the molecules present on the film and generating functional groups is important. Therefore, in this embodiment, a vacuum plasma treatment shown below is performed as the first surface modification treatment (described in detail later) to perform the process of cutting the molecules and adding functional groups. Figure 4 shows the configuration of a vacuum plasma treatment apparatus 100 suitable for this embodiment.
[0023] The vacuum plasma processing apparatus 100 may be, for example, a known vacuum plasma processing apparatus equipped with a high-frequency power supply 110, a pair of electrodes 120 in which a gas flow path is formed, a mounting table 130 on which a material to be processed (in this example, a low dielectric resin film) can be placed, a processing gas supply source 140 such as oxygen or argon, and a vacuum pump 150. The vacuum plasma processing apparatus 100 may further be equipped with a known magnetron mechanism capable of generating a magnetic field in any direction, as exemplified in, for example, Japanese Patent Application Laid-Open No. 2001-23958.
[0024] In this manner, in the vacuum plasma processing apparatus 100, the plasma processing gas PG is supplied as an activation gas from the processing gas supply source 140 via the electrode 120 to the low dielectric resin film 1 fixed on the mounting table 130 in the vacuum chamber. This causes the cleavage of the molecules on the surface of the low dielectric resin film 1 to proceed and also provides functional groups 2.
[0025] Here, the output condition in the vacuum plasma processing of this embodiment is 0.05 W / cm 2 ~2.00W / cm 2 It is preferable to change the type of gas supplied from the processing gas supply source 140 and the output conditions according to the material of the low dielectric resin film 1.
[0026] More specifically, for example, when the low dielectric resin film 1 is a non-fluorinated resin (COC, COP, SPS, LCP, PPS, PEEK, etc.), it is preferable to use oxygen plasma as the plasma treatment gas PG from the viewpoint of cleaving bond energy (C-H bonds, C-C bonds, etc.) and modifying (hereinafter also referred to as "generating") functional groups (hydroxyl groups and / or carboxyl groups).
[0027] Furthermore, for example, when the low dielectric resin film 1 is made of a fluororesin (such as the above-mentioned PTFE or PFA), it is necessary to cut C—F bonds, which have high bond energy, so that it is preferable to use argon plasma as the plasma treatment gas PG.
[0028] [Analysis of surface properties of low dielectric resin film after plasma treatment using XPS] As described above, in this embodiment, the vacuum plasma treatment is performed according to the type of low dielectric resin film 1, whereby the cleavage of the molecules proceeds on the surface of the low dielectric resin film 1 and the functional group 2 is imparted. In the present disclosure, the surface properties of the low dielectric resin film at this time are specified by the following method using the known XPS (X-ray photoelectron spectroscopy).
[0029] That is, in this disclosure, while there are differences in the patterns of decomposition of the above molecules and generation of functional groups for each resin depending on the type of low dielectric resin film, the surface properties were identified using the results of XPS analysis, broadly dividing the resins into non-fluorinated resins (COC, SPS, PPS, PEEK, etc.) and fluorinated resins (PFA, PTFE, etc.).
[0030] (α) Non-fluorinated resin (COC, SPS, PPS, PEEK, etc.) 5 illustrates the change in the XPS spectrum caused by the vacuum plasma treatment of the above-mentioned non-fluorinated resin (SPS as an example). In the present disclosure, the surface properties of the low dielectric resin film after the above-mentioned vacuum plasma treatment were specified by defining the area ratio of the peak derived from the C-C bond and the peak derived from the C-O bond using the XPS spectrum before and after the plasma treatment of the non-fluorinated resin (COC, SPS, PPS, PEEK, etc.).
[0031] In FIG. 5, "FM1" indicates the low dielectric resin film before plasma treatment (in this disclosure, the low dielectric resin film before plasma treatment is also referred to as the "original film"), "FM2" indicates the low dielectric resin film after plasma treatment, "FM3" indicates a film obtained by forming an electroless copper plating layer 5 on the low dielectric resin film after plasma treatment by the method described below, and then dissolving and removing the electroless copper plating layer, and "FM4" indicates the low dielectric resin film after undergoing the wet treatment described in the conventional method.
[0032] As an example, in the present disclosure, the surface properties are specified by defining the area ratio between the peak derived from the CC bond and the peak derived from the COO bond in FM1 and FM3, but the surface properties may be specified by the area ratio between the peak derived from the CC bond and the peak derived from the COO bond in FM1 and FM2.
[0033] In the present disclosure, the specific apparatus used for the XPS analysis was a PHI5000 VersaProbeII manufactured by ULVAC-PHI, Inc., and the above-mentioned area ratio was calculated in the following procedure. First, as shown by (α) in Figure 5, zero correction is performed at the positions of 282 eV and 295 eV to define the baseline. This makes it possible to efficiently identify the peaks of the above-mentioned functional groups and their ratios.
[0034] Next, as shown by (β) in Figure 5, the minimum intensity was subtracted from the maximum intensity, and the maximum intensity was normalized to a value of 1. This makes it possible to compare only the changes in the spectra before and after vacuum plasma treatment.
[0035] Next, the area ratio AR is calculated based on the following formula 1 using the XPS spectra of the low dielectric resin film 1 before and after the vacuum plasma treatment.
[0036] AR = (P area2 ) / (P area1 )... (Formula 1) however, P area2 : Peak area of 282.0 eV to 290.0 eV of low dielectric resin film after vacuum plasma treatment, obtained by waveform separation of C (carbon) in X-ray photoelectron spectroscopy (XPS) P area1 :P area1 Peak area of the original sheet before vacuum plasma treatment analyzed under the same conditions Let us assume that. The upper limit is set at 290.0 eV in the above because it is intended to more accurately measure the peaks of functional groups such as OH, COOH, COOOH, SO3H, SO2H, and SOH groups, and therefore to exclude the effects of aromatic rings and fluorine compounds that may appear in the range above 290 eV.
[0037] The inventors conducted extensive experiments and studies using various low dielectric resin films and found that a copper-clad laminate having the following characteristics can suppress transmission loss while ensuring high adhesion (3.5 N / cm or more in the tape peel test described below) at the interface with the electroless copper plating layer laminated directly on at least one side of the low dielectric film.
[0038] That is, the copper clad laminate of the present disclosure has a peak area (P) of 282.0 eV to 290.0 eV of the low dielectric resin film in a peak waveform obtained by waveform separation of C (carbon) in X-ray photoelectron spectroscopy (XPS) on the surface of the low dielectric resin film (wherein the low dielectric resin film has a relative dielectric constant of less than 3.2 at a frequency of 10 GHz and a dielectric loss tangent of 0.008 or less) that has been subjected to the first surface modification treatment. area2 ) and the peak area (P area1 ) area ratio (P area2 / P area1 ) is 0.90 or more and 2.00 or less. From the viewpoint of further increasing the adhesion at the interface between the low dielectric resin film and the electroless copper plating layer, area2 / P area1 ) is more preferably 1.00 or more, further preferably 1.05 or more, and particularly preferably 1.10 or more.
[0039] Furthermore, in the copper clad laminate of the present disclosure, in the low dielectric resin film that has been subjected to the first surface modification treatment, in the case of a non-fluorine-based low dielectric resin film (such as a liquid crystal polymer (LCP)) that does not contain fluorine and has a relative dielectric constant of 3.2 or more and a dielectric loss tangent of 0.008 or less at a frequency of 10 GHz, in order to ensure high adhesion at the interface between the low dielectric resin film and the electroless copper plating layer, the peak area (P area2 ) and the peak area (P area1 ) area ratio (P area2 / P area1 ) is 1.25 or more and 2.00 or less. From the viewpoint of further increasing the adhesion at the interface between the low dielectric resin film and the electroless copper plating layer, the area ratio (P area2 / P area1 ) is more preferably 1.35 or more, further preferably 1.40 or more, and particularly preferably 1.45 or more.
[0040] (β) Fluorine resin (PTFE, PFA, etc.) Figure 6 illustrates the change in the XPS spectrum of the above-mentioned fluororesin (PFA as an example) by the vacuum plasma treatment. As can be seen from the figure, unlike non-fluororesins, the fluororesin spectrum changes significantly because the C-F bonds are cut by the plasma treatment. For this reason, in the present disclosure, the surface properties of the low dielectric resin film after the above-mentioned vacuum plasma treatment were specified without using the original film by defining the peak intensity ratio PIR between the peak derived from the C-F bonds and other peaks using the XPS spectrum of the fluororesin after the plasma treatment.
[0041] In FIG. 6, "FM1" indicates the low dielectric resin film (original sheet) before the plasma treatment, "FM2" indicates the low dielectric resin film after the plasma treatment, "FM3" indicates a film obtained by forming an electroless copper plating layer 5 on the low dielectric resin film after the plasma treatment by the method described below and then dissolving and removing the electroless copper plating layer, and "FM4" indicates the low dielectric resin film after the wet treatment described in the conventional method.
[0042] In addition, the surface properties of the fluororesin were also specified using the above-mentioned PHI5000 VersaProbeII manufactured by ULVAC-PHI, Inc., and the peak intensity ratio PIR of the low dielectric resin film after plasma treatment was calculated by XPS according to the following procedure.
[0043] First, as shown by (α) in Figure 6, zero correction is performed at the positions of 282.0 eV and 295.0 eV to define the baseline. This makes it possible to efficiently identify the peaks and their ratios of the above-mentioned functional groups, as in the case of non-fluorinated resins. The reason for correcting at "the positions of 282.0 eV and 295.0 eV" in setting the baseline described above is to set the range to include peaks from the carbon chain (284.8 eV) to the CF3 group (294 eV) so that bonds of carbon-based compounds can be detected over a relatively wide range.
[0044] 6, the minimum intensity may be subtracted from the maximum intensity to normalize the maximum intensity to a value of 1. However, since the fluororesin in the low dielectric resin film 1 is specified by the peak intensity ratio, normalization is not essential and may be omitted as appropriate.
[0045] Next, as shown by (γ) in FIG. 6, the peak intensity ratio PIR is calculated based on the following formula 2 using the XPS spectrum of the low dielectric resin film 1 after the vacuum plasma treatment.
[0046] PIR = (Maximum intensity I from 283.0 to 288.0 eV MAX2 ) / (290.0-295.0 eV maximum intensity I MAX1 )... (Formula 2) In addition, in the formula 2, "the maximum intensity I MAX2 " identifies functional groups that have an influence on the main chain in the molecular structure of the film, and "maximum intensity I MAX1 identifies the functional groups that appear with the greatest intensity when part of the molecular structure is decomposed by vacuum plasma treatment.
[0047] The inventors conducted extensive experiments and studies using various low dielectric resin films and found that a copper-clad laminate having the following characteristics can suppress transmission loss while ensuring high adhesion (3.5 N / cm or more in the tape peel test described below) at the interface with the electroless copper plating layer laminated directly on at least one side of the low dielectric resin film.
[0048] That is, as can be seen from FIG. 6, one of the characteristics of the copper clad laminate of the present disclosure is that, in the peak waveform obtained by waveform separation of C (carbon) in X-ray photoelectron spectroscopy (XPS) on the surface of a low dielectric resin film (a fluororesin having a relative dielectric constant of less than 3.2 at a frequency of 10 GHz and a dielectric tangent of 0.008 or less) that has undergone the first surface modification treatment described above, the peak waveform has at least a peak between 283.0 eV and 288.0 eV.
[0049] In addition, the fluororesin suitable for this embodiment is one having a maximum peak intensity (I MAX2 ) and the maximum intensity of the peak between 290.0 eV and 295.0 eV (I MAX1 ) and the intensity ratio (I MAX2 / I MAX1 ) is preferably 1.00 or more. From the viewpoint of further increasing the adhesion at the interface between the low dielectric resin film and the electroless copper plating layer, it is preferable that the strength ratio (I MAX2 / I MAX1 ) is more preferably 2.00 or more, further preferably 3.00 or more, and particularly preferably 4.00 or more.
[0050] In this manner, in the present disclosure, by subjecting the surface of the low dielectric resin film 1 to a vacuum plasma treatment, functional groups 2 (hydroxyl and / or carboxyl groups) are provided at the interface between the low dielectric resin film 1 and the electroless copper plating layer 5 (see FIG. 3). Note that the "functional group containing a hydroxyl and / or carboxyl group" provided at the interface between the low dielectric resin film 1 and the electroless copper plating layer 5 is not limited to this form. Furthermore, if a "functional group containing a hydroxyl group" is provided, a "functional group containing a carboxyl group" does not have to be provided. Also, the reverse may be true. Furthermore, both a "functional group containing a hydroxyl group" and a "functional group containing a carboxyl group" may be provided. In order to specify the surface properties of the low dielectric resin film 1 after the plasma treatment, in this disclosure, the surface properties are specified by the above-mentioned method using a spectrum by a known XPS.
[0051] [Electroless copper plating layer] Returning to Fig. 1, the electroless copper plating layer 5 in this embodiment is preferably formed by a known electroless copper plating process. That is, since the low dielectric resin film 1 has insulating properties, a copper plating layer is formed on the film by the above-mentioned electroless copper plating process. Note that this electroless copper plating layer 5 may be a seed layer when manufacturing a flexible circuit board by a semi-additive method (SAP method or MSAP method), a subtractive method, a full additive method, or the like.
[0052] In this embodiment, the electroless copper plating layer 5 may be a plating of Cu alone, or may be a copper alloy plating containing a predetermined amount or more of copper. Examples of copper alloys include Cu-Ni alloys, Cu-Zn alloys, and Cu-Sn alloys. In this embodiment, such copper alloy plating is also included in the "copper plating". In this case, the Cu content in the electroless copper plating layer 5 is preferably 99.5 wt % or more, more preferably 99.6 wt % or more, and further preferably 99.7 wt % or more.
[0053] Furthermore, when the electroless copper plating layer 5 is formed of a Cu-Ni alloy, the Ni content is 3 wt% or less, preferably 0.01 to 3 wt%, more preferably 0.01 to 1.5 wt%, and even more preferably 0.01 to 0.3 wt%. When the electroless copper plating layer 5 is a Cu-Ni alloy, it is preferable to include Ni, which has a higher plating deposition rate than Cu, because this suppresses internal stress in the plating layer and therefore suppresses blisters.
[0054] If the amount of Ni in the Cu-Ni alloy exceeds 3 wt%, magnetism may occur in the Cu circuit, increasing transmission loss, and etching may become complicated when forming copper wiring, so the amount of Ni in the Cu-Ni alloy is preferably 3 wt% or less. If the amount of Ni in the Cu-Ni alloy falls below 0.01 wt%, plating deposition deteriorates. The Ni content of the electroless copper plating layer 5 can be measured by known methods such as an X-ray fluorescence analyzer (XRF) or an inductively coupled plasma (ICP) analyzer.
[0055] In this embodiment, a known plating bath may be used in the electroless copper plating step for forming the above-mentioned electroless copper plating layer 5 on the low dielectric resin film 1, as long as it is capable of forming the electroless copper plating layer 5 having a predetermined thickness. As an example, the electroless copper plating bath used in this embodiment may be an EDTA bath, a Rochelle bath, a triethanolamine bath, or the like. In addition, the thickness of the electroless copper plating layer 5 in this embodiment is preferably in the range of 50 nm to 1000 nm from the viewpoint of production efficiency and cost, more preferably 50 nm to 500 nm, and further preferably 50 nm to 300 nm.
[0056] [Adhesion strength between low dielectric resin film and electroless copper plating layer] Next, a method (one example) for evaluating the adhesion strength of the electroless copper plating layer 5 formed on the low dielectric resin film 1 using the above-mentioned method will be described. That is, in the embodiment, the following tape peeling test is applied as the method for evaluating the above-mentioned adhesion strength. This test conforms to the plating adhesion test method described in JIS H 8504 (1999) and is a known method for examining the adhesion of plating by attaching an adhesive tape to the plated surface and then rapidly and strongly peeling it off.
[0057] The test tape is an adhesive tape specified in JIS Z 1522, and can have a nominal width of 12 to 19 mm. The adhesive strength of this test tape is specified as approximately 8 N (i.e. 3.48 N / cm) per 25 mm width. During the test, an electroless copper plating layer 5 is directly laminated onto a low dielectric resin film 1 by the method of this embodiment, and then a test tape is attached onto the electroless copper plating layer 5, and then this is quickly and strongly peeled off.
[0058] At this time, the surface of the electroless copper plating layer 5 to which the test tape is adhered is used as the test target surface, and if any plating remains on the adhesive surface of the peeled test tape, it is evaluated as having poor adhesion. From the above-described results of the tape peeling test, it can be estimated that the adhesion strength between the low dielectric resin film 1 and the electroless copper plating layer 5 in this embodiment is 3.5 N / cm or more.
[0059] [others] As shown in FIG. 2, this embodiment may be implemented as a copper clad laminate 20 in which an electrolytic copper plating layer 6 is further formed on the electroless copper plating layer 5. That is, for example, when a known flexible circuit board is manufactured by a semi-additive method, the electroless copper plating layer 5 may be used as a seed layer, and after forming a resist pattern, an electrolytic copper plating layer 6 may be further formed by a known method. As an example, a known copper sulfate bath or copper pyrophosphate bath can be applied as an electrolytic copper plating step for forming the electrolytic copper plating layer 6. In addition, the electrolytic plating conditions (pH, temperature, current density, immersion time, etc.) can be appropriately selected based on the desired thickness of the electrolytic plating layer, etc.
[0060] Furthermore, the copper clad laminate 10 in this embodiment is formed by directly laminating the electroless copper plating layer 5 on the low dielectric resin film 1 as described above, but for example, a known protective layer for preventing oxidation may be formed on the surface of the electroless copper plating layer 5. Similarly, in this embodiment, the copper clad laminate 20 may be formed in which a known protective layer is formed on the electrolytic copper plating layer 6 described above.
[0061] <Method of manufacturing copper clad laminate> Next, a method for producing the copper clad laminate 10 of this embodiment will be described with reference to FIG. That is, first, in step 1, as a first surface modification process, a vacuum plasma treatment is performed on the above-mentioned low dielectric resin film 1. As an example, the above-mentioned vacuum plasma treatment apparatus 100 is used to supply a plasma treatment gas according to the material of the low dielectric resin film to the film surface. As a result, a part of the molecular structure on the surface of the low dielectric resin film 1 is decomposed, and the above-mentioned functional group 2 is imparted to the surface of the low dielectric resin film 1.
[0062] In the subsequent step 2, as a second surface modification step, a positive charge is applied to the surface of the low dielectric resin film 1, for example, as a Pd-supported layer 3, and then a negative charge is applied. By interposing such a Pd-supported layer 3 between the film and the electroless copper plating layer, it becomes possible to more reliably maintain the catalyst nuclei 4, which serve as the nuclei for plating deposition, on the film.
[0063] In the subsequent step 3, a catalyst adsorption step, catalytic nuclei 4 are adsorbed onto the low dielectric resin film 1 on which the Pd support layer 3 has been formed. In the subsequent step 4, an electroless copper plating layer 5 is formed on the surface of the low dielectric resin film 1 on which the catalytic nuclei 4 have been adsorbed. As an example, the electroless copper plating layer 5 may be formed using a known plating bath such as an EDTA bath, a Rochelle bath, or a triethanolamine bath.
[0064] Through the above steps, a copper clad laminate 10 is produced, which includes a low dielectric resin film 1 having a relative dielectric constant of less than 3.2 and a dielectric loss tangent of 0.008 or less at a frequency of 10 GHz, and an electroless copper plating layer 5 directly laminated on at least one surface of the low dielectric resin film 1. In particular, when the low dielectric resin film 1 is made of a non-fluorine-based resin, the peak area (P area2 ) and the peak area (P area1 ) area ratio (P area2 / P area1 ) is 0.90 or more and 2.00 or less. Furthermore, when the low dielectric resin film 1 is made of a fluororesin, a copper clad laminate 10 is obtained that has at least a peak at 283.0 eV to 288.0 eV in the peak waveform obtained by waveform separation of C (carbon) by X-ray photoelectron spectroscopy (XPS) on the surface of the low dielectric resin film 1.
[0065] Furthermore, by undergoing the above steps, a non-fluorine-based low dielectric resin film 1 (such as a liquid crystal polymer (LCP)) that does not contain fluorine and has a relative dielectric constant of 3.2 or more and a dielectric loss tangent of 0.008 or less at a frequency of 10 GHz, and an electroless copper plating layer 5 on at least one surface of the low dielectric resin film 1, and a peak area (P area2 ) and the peak area (P area1 ) area ratio (P area2 / P area1 ) is 1.25 or more and 2.00 or less.
[0066] In this embodiment, the description has been given up to the formation of the electroless copper plating layer 5 in step 4. However, the present disclosure is not limited to the structure of the copper clad laminate 10 described above, and may subsequently include a heating (annealing) step of heating the copper clad laminate 10 on which the electroless copper plating layer 5 has been formed. Furthermore, after the heating (annealing) step of heating the copper clad laminate 10, the disclosure may further include a resist patterning step of forming a resist on the electroless copper plating layer 5, an electrolytic copper plating step of forming an electrolytic copper plating layer 6 between the patterned resist, a resist removal step of removing the patterned resist, and the like.
[0067] Thus, the method for producing a copper clad laminate in this embodiment is a method for producing a copper clad laminate by forming an electroless copper plating layer on a low dielectric resin film having a relative dielectric constant of 3.5 or less at a frequency of 10 GHz and a dielectric tangent of 0.008 or less, and is characterized by including at least a step of performing a first surface modification on the surface of the low dielectric resin film by vacuum plasma treatment, and an electroless copper plating step of directly laminating an electroless copper plating layer on the side of the low dielectric resin film that has been surface modified by the vacuum plasma treatment. Each step will be described in detail below.
[0068] [Plasma treatment of low dielectric resin film: First surface modification process] First, in the first surface modification step, a vacuum plasma treatment is performed on at least one surface of a low dielectric resin film 1 using a vacuum plasma treatment device 100 as illustrated in Fig. 4. The vacuum plasma treatment can be performed, for example, by preparing a low dielectric resin film 1, using the joining surface of the low dielectric resin film 1 as one electrode grounded to earth, and applying an alternating current of 1 MHz to 50 MHz between the joining surface and another electrode supported insulated to generate a glow discharge. During the vacuum plasma treatment, the earthed electrode takes the form of a cooling roll to prevent the temperature of the transported material from rising.
[0069] In the vacuum plasma treatment in the first surface modification step described above, the surface of the low dielectric resin film 1 to be joined is subjected to a vacuum plasma treatment using a plasma treatment gas (active gas or inert gas) under vacuum, whereby molecules present on the low dielectric resin film 1 are cut to generate functional groups, making it possible to realize good adhesion between the low dielectric resin film 1 and the electroless copper plating layer 5. As the active gas, oxygen or a mixed gas containing oxygen can be used. As the inert gas, argon, neon, xenon, krypton, etc., or a mixed gas containing at least one of these can be used.
[0070] Here, the output condition in the vacuum plasma processing of this embodiment is 0.05 W / cm 2 ~2.00W / cm 2 It is preferable to change the type of gas supplied from the processing gas supply source 140 and the output conditions according to the material of the low dielectric resin film 1.
[0071] More specifically, for example, when the low dielectric resin film 1 is a non-fluorine-based resin (COC, COP, SPS, LCP, PPS, PEEK, etc.), it is preferable to use oxygen as the plasma treatment gas from the viewpoint of breaking the bond energy (CH bond or CC bond, etc.) and generating functional groups (hydroxyl group and / or carboxyl group). In particular, when the low dielectric resin film 1 is a cycloolefin-based resin (COC, COP, etc. as described above), it is more preferable to perform oxygen plasma treatment with a relatively low output as the output condition of the plasma treatment gas, since not much energy is required to break the above-mentioned molecules. In addition, when the low dielectric resin film 1 is a resin containing an aromatic ring (SPS, LCP, PPS, PEEK, etc. as described above), it is more preferable to perform oxygen plasma treatment with a relatively high output as the output condition of the plasma treatment gas, since relatively strong energy is required to break the aromatic ring molecules.
[0072] Furthermore, for example, when the low dielectric resin film 1 is a fluororesin (such as the above-mentioned PTFE or PFA), it is necessary to cut the C—F bond, which has high bond energy, so that it is preferable to use argon (Ar) as the plasma treatment gas.
[0073] It is preferable that the above-described vacuum plasma processing apparatus 100 further includes a magnetron mechanism capable of generating a magnetic field in any direction. In the method for producing a copper clad laminate in this embodiment, a magnetron mechanism is installed to locally confine plasma to the surface of the low dielectric resin film 1, and the output of the plasma treatment gas is set to 0.05 W / cm. 2 ~2.00W / cm 2 At a low output, it is possible to increase the adhesion between the low dielectric resin film 1 and the electroless copper plating layer 5 while suppressing thermal deformation of the low dielectric resin film 1 during plasma treatment (controlling the smoothness and flatness of the film surface).
[0074] When the above-mentioned magnetron mechanism is installed, the output condition of the plasma processing gas is preferably 0.05 W / cm.2 ~1.50W / cm 2 , and more preferably 0.05 W / cm 2 ~1.20W / cm 2 , and particularly preferably 0.10 W / cm 2 ~1.20W / cm 2 It is preferable that the treatment time of the plasma treatment gas is 50 seconds to 1500 seconds, more preferably 50 seconds to 1350 seconds, and further preferably 80 seconds to 1350 seconds. By controlling the treatment time within the above range, it is possible to improve the adhesion between the low dielectric resin film 1 and the electroless copper plating layer 5, and the surface smoothness of the low dielectric resin film 1, which is preferable. On the other hand, when the output conditions of the plasma treatment gas and the treatment time are below the lower limit of the above range, it is not preferable because sufficient adhesion between the low dielectric resin film 1 and the electroless copper plating layer 5 cannot be obtained. On the other hand, when the output conditions of the plasma treatment gas and the treatment time are above the upper limit of the above range, it is not preferable because the smoothness or flatness of the surface of the low dielectric resin film 1 may be impaired, resulting in an increased transmission loss.
[0075] [Charging low dielectric resin film after plasma treatment: second surface modification process] After the low dielectric resin film 1 is subjected to the vacuum plasma treatment by the above-mentioned method, a second surface modification step may be performed, as shown in Fig. 3, in which a Pd-supported layer 3 (positive and negative charges) is provided to the side of the low dielectric resin film 1 that has been subjected to the first surface modification treatment. By providing charges as the Pd-supported layer 3, it is possible to improve the adhesion of catalyst cores 4 (metallic palladium Pd in this example) to the film, which will be described later.
[0076] That is, in order to form an electroless copper plating layer 5 on the low dielectric resin film 1, it is preferable that catalytic nuclei that serve as nuclei for plating deposition are present on the film. From this viewpoint, in order for the catalytic nuclei (metallic palladium Pd) to adhere firmly to the film, it is preferable that the surface of the low dielectric resin film 1 has at least a negative charge after the second surface modification step.
[0077] Therefore, in the second surface modification step of this embodiment, it is preferable to impart a positive charge to the surface of the low dielectric resin film 1, and then impart a negative charge to the surface to which the positive charge has been imparted. By going through these steps, it becomes possible to reliably attach a negative charge to the surface of the low dielectric resin film 1.
[0078] As a specific method for imparting a positive charge to the surface of the low dielectric resin film 1, for example, a method of immersing the film in a known cationic surfactant or a method of contacting the low dielectric resin film 1 with the cationic surfactant by spraying the film may be applied.
[0079] In addition, specific methods for imparting a negative charge to the surface of the low dielectric resin film 1 include, for example, a method of immersing the film in a known anionic surfactant or a method of contacting the anionic surfactant with the low dielectric resin film 1 by spraying the film. By going through the above-mentioned method, as shown in FIG. 3, a Pd-supported layer 3 is formed on the functional group 2 of the low dielectric resin film 1 that has been subjected to the vacuum plasma treatment.
[0080] [Adding catalytic nuclei to low dielectric resin films: catalyst adsorption treatment] Next, the catalyst adsorption treatment in this embodiment will be described. That is, the catalyst adsorption treatment in this embodiment is a process of adsorbing catalyst nuclei 4, which serve as nuclei for plating deposition in the electroless copper plating layer, onto the low dielectric resin film 1 whose surface has been given electric charges by the above-mentioned second surface modification process, as exemplified in FIG. 7.
[0081] More specifically, the catalyst nuclei (metallic palladium Pd in this example) can be adsorbed on the surface of the low dielectric resin film 1 by, for example, contacting a known catalyst liquid with the surface of the low dielectric resin film 1 by a known method. Examples of such catalyst nuclei include, in addition to the above-mentioned metallic palladium Pd, Cu, Ni, Ag, etc. Also, as the above-mentioned known catalyst liquid, for example, a tin-palladium-based or palladium colloid-based catalyst liquid, etc. can be used.
[0082] In the above-mentioned catalyst adsorption treatment, the amount of catalyst applied to the low dielectric resin film 1 is 30 μg / dm in terms of metallic palladium. 2 Regarding the lower limit of the catalyst, the less the better, taking into consideration the etching during circuit formation, but it is necessary to add the catalyst to such an extent that the electroless copper plating layer is well formed, and the lower limit is 5 μg / dm 2 More than this is preferable. In the above-mentioned catalyst adsorption process, the low dielectric resin film may be immersed for several minutes in an aqueous solution (e.g., at 25°C) containing, as a catalyst activator (reducing agent), for example, 1 g / L of dimethylamine borane (DMAB) and 6 g / L of boric acid to perform a reduction treatment of the catalyst cores 4.
[0083] [Formation of electroless copper plating layer 5 on low dielectric resin film: electroless copper plating process] Next, the electroless copper plating process of this embodiment will be described. That is, the electroless copper plating process of this embodiment is a process of forming an electroless copper plating layer on the surface of the low dielectric resin film 1 on which the above-mentioned catalytic nuclei 4 are adsorbed, using a known bath such as an EDTA bath, a Rochelle bath, or a triethanolamine bath as an electroless copper plating bath.
[0084] The immersion time of the low dielectric resin film 1 in the electroless copper plating bath may be appropriately determined so that the thickness of the electroless copper plating layer 5 becomes 50 nm to 1000 nm. Furthermore, the plating layer formed in this electroless copper plating process is not limited to plating of simple Cu, but may be copper alloy plating, for example, a Cu-Ni alloy, a Cu-Zn alloy, a Cu-Sn alloy, etc. By carrying out the above steps, the copper clad laminate 10 of this embodiment is manufactured. EXAMPLES
[0085] Next, the present invention will be described more specifically with reference to examples. <Example 1> First, COC (Coxec TCS-1, Kuraray Industries, Ltd., thickness: 25 μm) was prepared as low dielectric resin film 1. As for electrical properties, the relative dielectric constant at 10 GHz was 2.3, and the dielectric loss tangent at 10 GHz was 0.0013.
[0086] Next, as a first surface modification step, oxygen (O2) plasma treatment was performed on both sides of the prepared low dielectric resin film 1 by the above-mentioned vacuum plasma treatment device 100. The plasma treatment conditions were as follows: the vacuum plasma treatment device 100 was equipped with a magnetron mechanism, and the output was set to 0.30 W / cm 2 The processing time was 90 seconds.
[0087] Next, as a second surface modification step, both sides of the low dielectric resin film 1 were immersed in an aqueous solution of 10 g / L of a cationic surfactant for 2 minutes to adsorb positive charges. After immersion and rinsing with water, the film was immersed in an aqueous solution of 3 g / L of an anionic surfactant for 1 minute. In this way, the film was allowed to adsorb positive charges and then negative charges.
[0088] Next, in the catalyst adsorption process, the plate was immersed in an aqueous solution of palladium chloride (PdCl2) (2 g / L, pH 12, 40°C) as a plating catalyst for 5 minutes, and then rinsed with water. Furthermore, the plate was immersed in an aqueous solution (25°C) containing 1 g / L of dimethylamine borane (DMAB) and 6 g / L of boric acid as a catalyst activator (reducing agent) for 5 minutes, and then rinsed with water.
[0089] Thereafter, in the electroless copper plating step, an electroless Cu-Ni plating layer was formed to a thickness of 200 nm in an electroless plating bath under the following electroless plating conditions.
[0090] [Electroless plating conditions] Bath composition: Copper sulfate 7.5g / L Sulfuric acid 0.6g / L Nickel sulfate 0.006g / L Rochelle salt 20g / L IPA 0.5g / L Sodium hydroxide 6.8g / L Formaldehyde 2.2g / L pH: 12.5 Bath temperature: 45℃
[0091] In this example, a copper clad laminate 10 was produced by the above-mentioned method, in which an electroless copper plating layer 5 was formed on a low dielectric resin film 1. Note that the heating (annealing) treatment of the obtained copper clad laminate 10 was omitted.
[0092] <Analysis of surface properties> In this example, a film (corresponding to "FM3" in FIG. 5) was produced by dissolving the electroless copper plating layer 5 of the obtained copper clad laminate 10 with a known dissolving agent (e.g., 30% nitric acid solution, etc.). The surface properties of the low dielectric resin film 1 after the plasma treatment of this film were analyzed using the above-mentioned XPS (X-ray polymer spectroscopy).
[0093] As a result, in this embodiment, in the peak obtained by waveform separation of C (carbon) in X-ray photoelectron spectroscopy (XPS), the peak area (P area2 ), and the peak area (P area1 ) and the area ratio (P area2 / P area1 ) and the result was 1.39.
[0094] <Tape peel strength> A test tape (manufactured by Nichiban Co., Ltd., width 25 mm) was applied to the surface of the electroless copper plating layer 5 of the copper clad laminate 10 on which the electroless copper plating layer 5 was formed, and then the tape was peeled off in accordance with the "plating adhesion test method" described in JIS H 8504 (1999) to carry out the above-mentioned tape peel test. The test tape is an adhesive tape specified in JIS Z 1522, and one with a nominal width of 12 to 19 mm can be used. The adhesive strength of this test tape is specified to be about 8 N (i.e., 3.48 N / cm) per 25 mm width. If plating was confirmed to be adhering to the adhesive surface of the test tape after it was peeled off, the adhesion was deemed poor and the evaluation result was given an ×; if no plating was confirmed to be adhering, the evaluation result was given an ⊚ (estimated to be 3.5 N / cm or more); and if plating was only confirmed to be adhering partially (to a level that does not cause any problems in practical use), the evaluation result was given an ◯.
[0095] <Surface roughness Ra after peeling off electroless copper plating layer 5> The electroless copper plating layer 5 of the obtained copper clad laminate 10 (electroless copper plating layer 5 thickness: 200 nm) was peeled off using the same solvent as described above to expose the low dielectric resin film 1. The surface roughness (arithmetic mean roughness Ra) of the exposed low dielectric resin film 1 was measured with an atomic force microscope (Bruker DimensionIcon) at a viewing angle of 10 μm × 10 μm.
[0096] <Metal Content (wt%) in Electroless Copper Plating Layer 5> The surface of the low dielectric resin film 1 was cut into a piece measuring 20 mm x 20 mm, and the element concentration ratio in the depth direction was calculated in 10 nm increments in SiO2 terms using an X-ray photoelectron spectrometer (ULVAC-PHI, VersaProbeII, X-ray source: Al, analysis area: 100 μm). The Cu concentration [Cu / (Cu+Ni)] among the metal elements (Cu, Ni) when the element concentration of Cu was maximum was calculated in weight percent. The results summarized above are shown in Tables 1, 2, and 4, respectively.
[0097] <Example 2> The same procedure as in Example 1 was carried out except that the plasma processing conditions were as shown in Table 1. Specifically, the plasma processing conditions were as follows: the vacuum plasma processing apparatus 100 was equipped with a magnetron mechanism, and the output was 0.09 W / cm 2 The processing time was 90 seconds. The results summarized above are shown in Tables 1 and 2, respectively.
[0098] <Example 3> The same procedure as in Example 1 was carried out except that the low dielectric resin film 1 was SPS (Oidys CN, manufactured by Kurabo Industries, Ltd., thickness: 50 μm) and the plasma treatment conditions were as shown in Table 1. Specifically, the plasma treatment conditions were a vacuum plasma treatment device 100 equipped with a magnetron mechanism, and an output of 0.60 W / cm 2 The processing time was 90 seconds. The results summarized above are shown in Tables 1, 2, and 4, respectively.
[0099] <Example 4> The same procedure as in Example 3 was carried out except that the plasma processing conditions were as shown in Table 1. Specifically, the plasma processing conditions were as follows: the vacuum plasma processing apparatus 100 was equipped with a magnetron mechanism, and the output was 0.09 W / cm 2 The processing time was 90 seconds. The results summarized above are shown in Tables 1 and 2, respectively.
[0100] <Example 5> The same procedure as in Example 1 was carried out, except that the low dielectric resin film 1 was PPS (TORELINA 3030, manufactured by Toray Industries, Inc., thickness: 50 μm) and the plasma treatment conditions were as shown in Table 1. Specifically, the plasma treatment conditions were a vacuum plasma treatment device 100 equipped with a magnetron mechanism, an output of 0.60 W / cm 2 The processing time was 90 seconds. The results summarized above are shown in Tables 1, 2, and 4, respectively.
[0101] <Example 6> The same procedure as in Example 5 was carried out except that the plasma treatment conditions were as shown in Table 1. Specifically, the plasma treatment conditions were as follows: the vacuum plasma treatment apparatus 100 was equipped with a magnetron mechanism, and the output was 0.30 W / cm 2 The processing time was 90 seconds. The results summarized above are shown in Tables 1 and 2, respectively.
[0102] <Example 7> The same procedure as in Example 1 was carried out, except that the low dielectric resin film 1 was PEEK (EXPEEK, manufactured by Kurabo Industries, Ltd., thickness: 50 μm) and the plasma treatment conditions were as shown in Table 1. Specifically, the plasma treatment conditions were a vacuum plasma treatment device 100 equipped with a magnetron mechanism, and an output of 0.60 W / cm 2 The processing time was 90 seconds. The results summarized above are shown in Tables 1, 2, and 4, respectively.
[0103] <Example 8> The same procedure as in Example 7 was carried out, except that the plasma treatment conditions were as shown in Table 1. Specifically, the plasma treatment conditions were as follows: the vacuum plasma treatment apparatus 100 was equipped with a magnetron mechanism, and the output was 0.09 W / cm 2 The processing time was 90 seconds. The results summarized above are shown in Tables 1 and 2, respectively.
[0104] <Example 9> The same procedure as in Example 1 was carried out, except that the low dielectric resin film 1 was an LCP (Vecstar CTQ, manufactured by Kuraray Co., Ltd., thickness: 50 μm) and the plasma treatment conditions were as shown in Table 1. Specifically, in this example, the vacuum plasma treatment device 100 was not equipped with the magnetron mechanism described above, and the output was set to 0.31 W / cm 2 The processing time was set to 1260 seconds. The results summarized above are shown in Tables 1 and 2, respectively.
[0105] <Example 10> The same procedure as in Example 9 was carried out except that the plasma processing conditions were as shown in Table 1. Specifically, the vacuum plasma processing apparatus 100 was not equipped with the magnetron mechanism described above as in Example 9, and the output was set to 0.09 W / cm 2 The processing time was set to 420 seconds. The results summarized above are shown in Tables 1, 2, and 4, respectively.
[0106] <Example 11> The same procedure as in Example 1 was carried out except that the low dielectric resin film 1 was PFA (Fluon+ EA-2000, manufactured by AGC Inc., thickness: 50 μm), argon (Ar) gas was used as the plasma treatment gas, and the plasma treatment conditions were as shown in Table 1. Specifically, the plasma treatment conditions were a vacuum plasma treatment device 100 equipped with a magnetron mechanism, and an output of 0.60 W / cm 2 The processing time was 90 seconds.
[0107] In this example, a film (corresponding to "FM3" in FIG. 6) was produced by dissolving the electroless copper plating layer 5 of the obtained copper clad laminate 10 with a known dissolving agent. The surface properties of the low dielectric resin film 1 after the plasma treatment of this film were analyzed using the above-mentioned XPS (X-ray polymer spectroscopy).
[0108] As a result, in this embodiment, the low dielectric resin film after the plasma treatment was analyzed by XPS without using the original film. Specifically, the peak waveform obtained by waveform separation of C (carbon) in X-ray photoelectron spectroscopy (XPS) had at least a peak at 283.0 eV to 288.0 eV, and the maximum peak intensity (I MAX2 ), and the maximum intensity of the peak between 290.0 eV and 295.0 eV (I MAX1 ) was measured, and the peak intensity ratio (I MAX2 / I MAX1 ) was calculated to be 4.90. The results summarized above are shown in Tables 1, 3, and 4, respectively.
[0109] <Example 12> The same procedure as in Example 11 was carried out except that the plasma treatment conditions were as shown in Table 1. Specifically, the plasma treatment conditions were as follows: the vacuum plasma treatment apparatus 100 was equipped with a magnetron mechanism, and the output was 0.15 W / cm 2 The processing time was 90 seconds. The results summarized above are shown in Tables 1 and 3, respectively.
[0110] <Example 13> The same procedure as in Example 11 was carried out except that the low dielectric resin film 1 was made of PTFE (skived tape, manufactured by Chukoh Chemical Industries, Ltd., thickness: 50 μm). Specifically, the plasma treatment conditions were as follows: the vacuum plasma treatment device 100 was equipped with a magnetron mechanism, and the output was 0.60 W / cm 2 The processing time was 90 seconds. The results summarized above are shown in Tables 1, 3, and 4, respectively.
[0111] <Example 14> The same procedure as in Example 13 was carried out except that the plasma treatment conditions were as shown in Table 1. Specifically, the plasma treatment conditions were as follows: the vacuum plasma treatment apparatus 100 was equipped with a magnetron mechanism, and the output was 0.15 W / cm 2 The processing time was 90 seconds. The results summarized above are shown in Tables 1 and 3, respectively.
[0112] <Comparative Example 1> The first surface modification treatment was carried out in the same manner as in Example 1, except that the known wet treatment shown in Patent Documents 3 to 6 was carried out instead of the vacuum plasma treatment. The wet treatment involved immersion in a mixed solution of potassium hydroxide aqueous solution and monoethanolamine for 5 minutes to introduce carboxyl groups and / or hydroxyl groups to both surfaces, followed by immersion and water washing. The temperature of the mixed solution used was 45°C. The results summarized above are shown in Tables 1 and 2.
[0113] <Comparative Example 2> The same procedure as in Comparative Example 1 was carried out, except that the low dielectric resin film 1 was SPS (Oidys CN, manufactured by Kurabo Industries, Ltd., thickness: 50 μm). The results summarized above are shown in Tables 1 and 2.
[0114] <Comparative Example 3> The same procedure as in Comparative Example 1 was carried out, except that the low dielectric resin film 1 was PPS (TORELINA 3030, manufactured by Toray Industries, Inc., thickness: 50 μm). The results summarized above are shown in Tables 1 and 2.
[0115] <Comparative Example 4> The same procedure as in Comparative Example 1 was carried out, except that the low dielectric resin film 1 was made of PEEK (EXPEEK, manufactured by Kurabo Industries, Ltd., thickness: 50 μm). The results summarized above are shown in Tables 1 and 2.
[0116] <Comparative Example 5> The same procedure as in Comparative Example 1 was carried out, except that the low dielectric resin film 1 was an LCP (Vecstar CTQ, manufactured by Kuraray Co., Ltd., thickness: 50 μm). The results summarized above are shown in Tables 1 and 2.
[0117] <Comparative Example 6> The first surface modification treatment was carried out in the same manner as in Example 11, except that the known wet treatment shown in Patent Documents 3 to 6 was carried out instead of the vacuum plasma treatment. The wet treatment was the same as in Comparative Example 1. The results summarized above are shown in Tables 1 and 3.
[0118] <Comparative Example 7> The same procedure as in Comparative Example 6 was carried out, except that the low dielectric resin film 1 was made of PTFE (skived tape, manufactured by Chukoh Chemical Industries, Ltd., thickness: 50 μm). The results summarized above are shown in Tables 1 and 3.
[0119] <Comparative Example 8> The same procedure as in Comparative Example 1 was carried out, except that a heating (annealing) treatment was further carried out after the electroless copper plating layer 5 was formed. The results summarized above are shown in Tables 1 and 2.
[0120] <Comparative Example 9> The same procedure as in Comparative Example 8 was carried out, except that the low dielectric resin film 1 was SPS (Oidys CN, manufactured by Kurabo Industries, Ltd., thickness: 50 μm). The results summarized above are shown in Tables 1 and 2.
[0121] <Comparative Example 10> The same procedure as in Comparative Example 8 was carried out, except that the low dielectric resin film 1 was PPS (TORELINA 3030, manufactured by Toray Industries, Inc., thickness: 50 μm). The results summarized above are shown in Tables 1 and 2.
[0122] <Comparative Example 11> The same procedure as in Comparative Example 8 was carried out, except that the low dielectric resin film 1 was made of PEEK (EXPEEK, manufactured by Kurabo Industries, Ltd., thickness: 50 μm). The results summarized above are shown in Tables 1 and 2.
[0123] <Comparative Example 12> The same procedure as in Comparative Example 6 was carried out, except that a heating (annealing) treatment was further carried out after the electroless copper plating layer 5 was formed. The results summarized above are shown in Tables 1 and 3.
[0124] <Comparative Example 13> The same procedure as in Comparative Example 12 was carried out except that the low dielectric resin film 1 was made of PTFE (skived tape, manufactured by Chukoh Chemical Industries, Ltd., thickness: 50 μm). The results summarized above are shown in Tables 1 and 3.
[0125] [Table 1]
[0126] [Table 2]
[0127] [Table 3]
[0128] [Table 4] [Industrial Applicability]
[0129] The copper clad laminate of the present invention can ensure high adhesion at the interface between the low dielectric film and the electroless copper plating layer while suppressing transmission loss, and therefore it is clear that the copper clad laminate of the present invention is suitably applied to wiring boards and the like that require multilayer fine wiring. [Explanation of symbols]
[0130] 1. Low dielectric resin film 2 Functional group 3 Pd-supported layer 4. Catalytic core 5 Electroless copper plating layer 6 Electrolytic copper plating layer 10, 20 Copper clad laminate
Claims
1. a low dielectric resin film having a relative dielectric constant of less than 3.2 and a dielectric tangent of 0.008 or less at a frequency of 10 GHz; an electroless copper plating layer directly laminated on at least one surface of the low dielectric resin film; A copper clad laminate comprising:
2. A low dielectric resin film having a relative dielectric constant of 3.2 or more and a dielectric loss tangent of 0.008 or less at a frequency of 10 GHz, and an electroless copper plating layer on at least one surface of the low dielectric resin film, In the peak waveform obtained by waveform separation of C (carbon) in X-ray photoelectron spectroscopy (XPS) on the surface of the low dielectric resin film, the peak area (P area2 ) and the peak area (P area1 ) area ratio (P area2 / P area1 ) is 1.25 or more and 2.00 or less.
3. In the peak obtained by waveform separation of C (carbon) in X-ray photoelectron spectroscopy (XPS) on the surface of the low dielectric resin film, the peak area (P area2 ) and the peak area (P area1 ) and the area ratio (P area2 / P area1 2. The copper clad laminate of claim 1, wherein the coefficient of friction coefficient is 0.9 or more.
4. 2. The copper clad laminate according to claim 1, wherein the surface of the low dielectric resin film has at least a peak at 283.0 eV to 288.0 eV of the low dielectric resin film in peaks obtained by waveform separation of C (carbon) in X-ray photoelectron spectroscopy (XPS).
5. In the peak waveform, the maximum peak intensity (I MAX2 ) and the peak maximum intensity between 290.0 eV and 295.0 eV (I MAX1 ) and the intensity ratio (I MAX2 / I MAX1 5. The copper clad laminate according to claim 4, wherein the coefficient of friction coefficient is 1.00 or more.
6. The copper clad laminate according to any one of claims 1 to 5, wherein the average surface roughness Ra of the low dielectric resin film at the interface with the electroless copper plating layer is 1.0 nm to 100.0 nm.
7. The copper clad laminate according to any one of claims 1 to 5, wherein the adhesion strength between the low dielectric resin film and the electroless copper plating layer is 3.5 N / cm or more.
8. The copper clad laminate according to any one of claims 1 to 5, wherein the electroless copper plating layer has a thickness of 50 nm to 1000 nm.
9. The copper clad laminate according to any one of claims 1 to 5, wherein the Cu content in the electroless copper plating layer is 99.5 wt % or more.
10. A method for producing a copper clad laminate, comprising forming an electroless copper plating layer on a low dielectric resin film having a relative dielectric constant of 3.5 or less and a dielectric loss tangent of 0.008 or less at a frequency of 10 GHz, A step of performing a first surface modification treatment on the surface of the low dielectric resin film by a vacuum plasma treatment; an electroless copper plating step of directly laminating an electroless copper plating layer on the surface of the low dielectric resin film that has been surface-modified by the vacuum plasma treatment; A method for producing a copper clad laminate, comprising:
11. The method further includes a second surface modification step of applying an electric charge to the first surface modified surface side of the low dielectric resin film, and a catalyst adsorption step of adsorbing a catalyst nucleus to the surface side to which the electric charge is applied, The method for producing a copper clad laminate according to claim 10 , wherein the electroless copper plating layer is formed on the surface on which the catalytic nuclei are adsorbed.
12. The method for producing a copper clad laminate according to claim 11 , wherein the first surface modification step includes a step of providing a carboxyl group and / or a hydroxyl group to a surface of the low dielectric resin film.
13. The method for producing a copper clad laminate according to claim 12, wherein the low dielectric resin film is made of a resin that does not contain fluorine.
14. The method for producing a copper clad laminate according to claim 13 , wherein the vacuum plasma treatment is performed using oxygen as an activation gas.
15. The method for producing a copper clad laminate according to claim 12, wherein the low dielectric resin film is made of a resin containing fluorine.
16. The method for producing a copper clad laminate according to claim 15 , wherein the vacuum plasma treatment is performed using argon as an activation gas.
17. The output condition in the vacuum plasma treatment is 0.05 W / cm 2 ~2.00 W / cm 2 The method for producing a copper clad laminate according to any one of claims 10 to 16,
Citation Information
Patent Citations
Datsusuikikabaanorotsukusochi
JP1976086266A
Toothbrush
JP1987002905A
Plating method
JP2002256443A
Copper-clad laminate and method for producing same
WO2021039370A1
Copper-clad layered body and method for producing same
WO2022030644A1